Defect-driven oxygen reduction reaction (ORR) of carbon without any element doping. Issue 3 (18th January 2016) - Zhao, Xiaojun; Zou, Xiaoqin; Yan, Xuecheng; Brown, Christopher L.; Chen, Zhigang; Zhu, Guangshan; Yao, Xiangdong
Abstract : A "pure" porous carbon, lacking any elemental doping, exhibits excellent activity of oxygen reduction. Abstract : A porous carbon (PC) material, containing carbon and oxygen only, was synthesized via carbonisation of a Zn-MOF (IRMOF-8) at 950 °C. Interestingly, the derived materials of this reaction exhibit excellent electrocatalytic activity, molecular selectivity and long-term durability. The fact that this material, which is effectively a "pure" carbon, lacking any elemental doping, exhibits excellent oxygen reduction reaction (ORR) activity suggests that a mechanism not dependent on elemental doping is being utilised. We suggest the formation of defects arising from the removal of Zn atoms as a consequence of the calcination procedure play the critical role in this process.